Experience of long-term use of a specialized amino acid mixture without phenylalanine in children with phenylketonuria - L. V. Goroshko; I. A. Khasanov (Лечащий Врач)
A retrospective study of the efficacy, safety and tolerability of long-term use of a specialized amino acid mixture without phenylalanine (Phe) in children with phenylketonuria (PKU) was carried out. We analyzed data from 14 patients with PKU, including 4 boys and 10 girls. The average age at initiation of dietary therapy was 23 days. The average weight of children at birth was 3.69 ± 0.65 kg. The mean plasma Phe level at the time of birth was 10.05 ± 2.7 mg/dl, with repeated testing it was 20.29 ± 4.48 mg/dl. By the end of the first month of life, on the background of diet therapy, the mean plasma Phe concentration in children was 2.58 ± 2.01 mg/dL. Later (mainly at the 6th and 11th months of life), some fluctuations in Phe were observed in individual patients, which in all cases was associated with objective reasons (the period of teething, the introduction of complementary foods, etc.). By the first year of life, the average Phe level in the blood of patients was 3.94 ± 3.03 mg/dl. At the end of the follow-up period, 85.7% of patients had a target blood Phe level not exceeding 6.0 mg/dL (n = 12). In the course of individual growth and development, a systematic increase in body weight was observed in all children. By the first year of life, the majority of patients (92.86%) showed satisfactory indices of individual development with no weight deficit, which was observed in only one child. In turn, the use of diet therapy was characterized by its good tolerance. None of the studied patients had any dyspeptic symptoms, atopy or other adverse events associated with the use of the mixture. Based on the results of the study, it was concluded that the long-term use of the used specialized amino acid mixture without Phe in young children with PKU was good, safe and tolerable.